Symptom Severity, Anxiety, Family Support, and Resilience of Breast Cancer Patients Undergoing Chemotherapy - Hilman Syarif; Novi Afrianti; Dewiyuliana; Monaris Daralina; Syarifah Rauzatul Jannah (LPPM Universitas Prima Nusantara Bukittinggi, 2025)
Purpose: The objective of this study was to exploring the relationship of symptom severity, anxiety, and family support to the resilience of breast cancer patients undergoing chemotherapy. Method: This research is a quantitative correlation with a cross-sectional study design. The sample size was 107 breast cancer patients undergoing chemotherapy at hospitals in Aceh Province and selected non-randomly with consecutive sampling technique. Bivariate data analysis was Pearson correlation. Results: The results showed that there was a significant negative relationship between symptom severity with resilience (r -0.249; p 0.010), and anxiety with resilience (r -0.569; p < 0.001). There was a significant positive relationship between family support and resilience (r 0.184; p 0.049). Conclusions: Resilience of breast cancer patients undergoing chemotherapy is closely related to symptom severity, anxiety and family support. Recommendations, to oncology nurses in order to increase interventions, especially on factors that can reduce the severity of symptoms and anxiety of patients, also increase family support.